Thickness of keratinized tissue as an indicator of success in connective tissue operations - Necla Asli Kocak Oztug (Elsevier, 2021)
Aim or Purpose: To investigate how keratinized tissue thickness have an impact on clinical outcome of the subepithelial connective tissue graft with coronally advanced flap procedure in Miller Class I defects which previously grouped as having either "thick" or "thin" phenotypes. Materials and Methods: Recession defects were treated with the same surgical approach in both "thick" (n=18), "thin" (n=19) groups. Plaque index (PI), gingival index (GI), recession depth (RD), recession width (RW) and width of keratinized tissue (WKT) were recorded on baseline, 6. week, 3., 6., 9., and 12. months respectively. Probing depth (PD), clinical attachment level (CAL), thickness of keratinized tissue (TKT) of defects were recorded on baseline, 3., 6., 9. and 12. months. The percentage of root coverage was measured on 3., 6. and 12. months. Palatal mucosa thickness measurements were repeated on 6. and 12. months. Results: Compared to baseline, there was statistically significant decrease in CAL, RD and RW; and a significant increase in PD, WKT and TKT in both groups (p<0,05). TKT was the highest on 3. month, decreased till 9. month and became stable then. According to phenotypes, only defects of thin group's baseline TKT was positively correlated with the amount of thin group's root coverage. Conclusions: Within the results of this study success of root coverage in connective tissue operations is influenced by a threshold thickness of flap in the operation area only in thin phenotype group.